The human antibody response to the surface of Mycobacterium tuberculosis. - Casey C Perley; Marc Frahm; Eva M Click; Karen M Dobos; Guido Ferrari; Jason E Stout; Richard Frothingham (PLoS ONE)
Background Vaccine-induced human antibodies to surface components of Haemophilus influenzae and Streptococcus pneumonia are correlated with protection. Monoclonal antibodies to surface components of Mycobacterium tuberculosis are also protective in animal models. We have characterized human antibodies that bind to the surface of live M. tuberculosis. Methods Plasma from humans with latent tuberculosis (TB) infection (n = 23), active TB disease (n = 40), and uninfected controls (n = 9) were assayed by ELISA for reactivity to the live M. tuberculosis surface and to inactivated M. tuberculosis fractions (whole cell lysate, lipoarabinomannan, cell wall, and secreted proteins). Results When compared to uninfected controls, patients with active TB disease had higher antibody titers to the surface of live M. tuberculosis (Δ = 0.72 log10), whole cell lysate (Δ = 0.82 log10), and secreted proteins (Δ = 0.62 log10), though there was substantial overlap between the two groups. Individuals with active disease had higher relative IgG avidity (Δ = 1.4 to 2.6) to all inactivated fractions. Surprisingly, the relative IgG avidity to the live M. tuberculosis surface was lower in the active disease group than in uninfected controls (Δ =  -1.53, p = 0.004). Patients with active disease had higher IgG than IgM titers for all inactivated fractions (ratios, 2.8 to 10.1), but equal IgG and IgM titers to the live M. tuberculosis surface (ratio, 1.1). Higher antibody titers to the M. tuberculosis surface were observed in active disease patients who were BCG-vaccinated (Δ = 0.55 log10, p = 0.008), foreign-born (Δ = 0.61 log10, p = 0.004), or HIV-seronegative (Δ = 0.60 log10, p = 0.04). Higher relative IgG avidity scores to the M. tuberculosis surface were also observed in active disease patients who were BCG-vaccinated (Δ = 1.12, p < 0.001) and foreign-born (Δ = 0.87, p = 0.01). Conclusions/significance Humans with active TB disease produce antibodies to the surface of M. tuberculosis with low avidity and with a low IgG/IgM ratio. Highly-avid IgG antibodies to the M. tuberculosis surface may be an appropriate target for future TB vaccines.